Pemanfaatan Sumber Daya Lokal untuk Pencegahan Stunting di Desa Tosale - Jamal, Jamaluddin; Pitriani; Asriani; Novalina; Adrianton; Arwan (Jurnal Pengabdian, 2025)
Stunting, a growth failure issue in toddlers due to chronic malnutrition, has implications for reduced productivity and an increased risk of degenerative diseases later in life. Inadequate feeding practices and undernutrition are primary causes. To prevent stunting in Tosale Village, leveraging local resources is crucial for enhancing the nutritional quality of children. This community engagement program aimed to educate the community of Tosale Village about stunting and its prevention in at-risk infants through practical training in preparing supplementary food based on Moringa oleifera leaves, packaged as pudding. The training employed a direct practice method involving community members, particularly mothers who are members of the Supplementary Feeding Program (PMT). The core activity involved hands-on practice in making Moringa leaf pudding as an alternative supplementary food for stunting prevention, accompanied by the presentation of materials related to stunting and the benefits of Moringa oleifera. Ten mothers who were PMT cadres participated in this training. The results of the activity demonstrated an increase in participants' knowledge and skills in making Moringa leaf pudding as a nutritious supplementary food. The utilization of local resources such as Moringa oleifera through training in the preparation of varied supplementary foods warrants continued support. This activity provides an alternative for PMT cadre mothers in serving supplementary food that has the potential to prevent stunting in at-risk infants in Tosale Village. Similar training utilizing other local food ingredients is recommended to enrich the options for nutritious supplementary foods.